Identification and characterization of the first Escherichia coli strain carrying NDM-1 gene in China. - Zhiyuan Liu (Public Library of Science (PLoS), 2013)
New Delhi metallo-β-lactamase-1 (NDM-1), an acquired class B carbapenemase, is a significant clinical threat due to its extended hydrolysis of β-lactams including carbapenems. In this study, we identified the first confirmed clinical isolate of Escherichia coli BJ01 harboring bla(NDM-1) in China. The isolate is highly resistant to all tested antimicrobials except polymyxin. bla(NDM-1), bla(CTX-M-57), and bla TEM-1 were identified in the isolate. bla(NDM-1) was transferable to E. coli EC600 and DH5α in both plasmid conjugation experiments and plasmid transformation tests. BJ01 was identified as a new sequence type, ST224, by multilocus sequence typing. Analysis of genetic environment shows complex transposon-like structures surrounding the bla NDM-1 gene. Genetic analysis revealed that the region flanking bla(NDM-1) was very similar to previously identified NDM-positive Acinetobacter spp. isolated in China. The findings of this study raise attention to the emergence and spread of NDM-1-carrying Enterobacteriaceae in China.